Pengurusan seni : Kajian kes di muzium tekstil sarawak (MTS) - Rabuyah, Binti Brahim (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study focuses on the intention of introducing and uplifting textile museum Sarawak as museum institution, that is as a storage of local civilization artefacts in Sarawak state administration specifically and in Malaysia generally. The study was done in the perspectives of management poblems identification in the pemise, elaborating the collections available as cultural heritage, analyzing the museum management pactices in MTS as well as suggesting museum arts activities in relation to which will focus on the collections information, categorization and information gathering of the collections, the collection storage and information management of the collection as well as the infomation documentation in the form of multimedia, the operation and usage of the pemise, records keeping of all form and types of records, types of usage, and the museum archiving system.